2011
DOI: 10.1158/1078-0432.ccr-10-2243
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Amplifies Chemotherapy-Induced AMPK Activation and Antitumoral Growth

Abstract: Purpose: Metformin is a widely used antidiabetic drug whose anticancer effects, mediated by the activation of AMP-activated protein kinase (AMPK) and reduction of mTOR signaling, have become noteworthy. Chemotherapy produces genotoxic stress and induces p53 activity, which can cross-talk with AMPK/mTOR pathway. Herein, we investigate whether the combination of metformin and paclitaxel has an effect in cancer cell lines.Experimental Design: Human tumors were xenografted into severe combined immunodeficient (SCI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
191
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(220 citation statements)
references
References 49 publications
22
191
1
6
Order By: Relevance
“…Metformin may inhibit IkB and IKKa/b subunits and hence NF-kB and may prevent the translocation of NF-kB from the cytoplasm to the nucleus (31). Metformin seems to downregulate genes involved in mitosis and may act synergistically in this setting with taxanes (32). Metformin may also act via the DNA damage response mechanisms through ataxia telangiectasia mutated (ATM) and Chk2 (33), also potentially accounting for the cancer prevention effect.…”
Section: Mitochondrial Effectsmentioning
confidence: 99%
“…Metformin may inhibit IkB and IKKa/b subunits and hence NF-kB and may prevent the translocation of NF-kB from the cytoplasm to the nucleus (31). Metformin seems to downregulate genes involved in mitosis and may act synergistically in this setting with taxanes (32). Metformin may also act via the DNA damage response mechanisms through ataxia telangiectasia mutated (ATM) and Chk2 (33), also potentially accounting for the cancer prevention effect.…”
Section: Mitochondrial Effectsmentioning
confidence: 99%
“…Mazzone et al reported that diabetes patients with lung cancer who were previously treated with metformin or thiazolidinediones had a lower incidence of metastatic disease at the time of diagnosis and a reduced risk of death compared to those who did not receive the same treatment (4). Thereafter, the antiproliferative action of metformin was confirmed via in vivo and in vitro experiments in various cancer cell lines including breast (5)(6)(7)(8), prostate (9), pancreas (10), and ovarian cancer (11)(12)(13) as well as lung adenocarcinoma (8).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these findings, the precise mechanisms of the metformin-induced effects are not fully understood. In particular, controversy remains about whether metformin is apoptotic (6,10) or just cytostatic (5,9) and whether it kills cancer cells synergistically with cytotoxic agents including cisplatin (11,13), paclitaxel (8), and doxorubicin (17), or if it is antagonistic to cisplatin (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Combined use of metformin with chemotherapeutic agents such as cisplatin has also yielded clinical benefits (25,26). Regarding the anticancer mechanism, metformin appears to preferentially kill cancer-initiating/stem cells from glioblastoma (27), breast (28) and ovarian cancers (29) via AMPactivated protein kinase (AMPK) activation.…”
mentioning
confidence: 99%